ANALISIS KESULITAN BELAJAR SISWA DALAM MEMAHAMI BILANGAN BERPANGKAT PECAHAN - RUTH SAHANAYA MANIK; NAZLAH INDRI AGISTIA; DAN YUNISYIA PUJI ASTUTI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze students' learning difficulties in understanding fractional exponents in grade IX junior high school students. The type of research used is qualitative research with a descriptive approach. The research subjects consisted of grade IX students who were selected based on the results of a diagnostic test on fractional exponents. Data collection techniques included tests, interviews, observations, and documentation. Data were analyzed using the Miles and Huberman model which includes the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that students experience several types of difficulties in learning fractional exponents, namely: (1) difficulty in understanding concepts, indicated by students' inability to interpret fractional exponents as roots and powers; (2) difficulty in using principles, characterized by errors in applying the properties of operations on exponents in practice questions; and (3) difficulty in solving verbal problems, where students are less able to transform story information into appropriate mathematical models. Factors causing learning difficulties include low mastery of the prerequisites for fractional operations, minimal in-depth understanding of concepts, and learning strategies that still focus on memorizing procedures. Efforts to overcome these difficulties include providing remedial guidance, using visual or concrete media, providing gradual practice, and conceptual-based learning.